Inflammation in Myocardial Ischemia/Reperfusion Injury: Underlying Mechanisms and Therapeutic Potential - Jamie Francisco; Dominic P. Del Re (MDPI AG, 2023)
Acute myocardial infarction (MI) occurs when blood flow to the myocardium is restricted, leading to cardiac damage and massive loss of viable cardiomyocytes. Timely restoration of coronary flow is considered the gold standard treatment for MI patients and limits infarct size; however, this intervention, known as reperfusion, initiates a complex pathological process that somewhat paradoxically also contributes to cardiac injury. Despite being a sterile environment, ischemia/reperfusion (I/R) injury triggers inflammation, which contributes to infarct expansion and subsequent cardiac remodeling and wound healing. The immune response is comprised of subsets of both myeloid and lymphoid-derived cells that act in concert to modulate the pathogenesis and resolution of I/R injury. Multiple mechanisms, including altered metabolic status, regulate immune cell activation and function in the setting of acute MI, yet our understanding remains incomplete. While numerous studies demonstrated cardiac benefit following strategies that target inflammation in preclinical models, therapeutic attempts to mitigate I/R injury in patients were less successful. Therefore, further investigation leveraging emerging technologies is needed to better characterize this intricate inflammatory response and elucidate its influence on cardiac injury and the progression to heart failure.